Akuntabilitas Kinerja Percepatan Penurunan Stunting di Kabupaten Buton Selatan - Tenri, Andi; Said, Risal; Abidin, Zainul (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study aims to describe performance accountability in accelerating stunting reduction in South Buton District, concerning four main indicators: strategic planning, performance measurement, performance reporting, and utilization of performance data. Using a qualitative method with a descriptive approach, this research was conducted in South Buton District with 8 informants from Regional Apparatus Organizations that manage stunting. Data were collected through interviews and documentation, while data analysis was done by data presentation, reduction, and conclusion drawing. The results showed that performance accountability for accelerating stunting reduction was not optimal. Strategic planning has not fully integrated stunting reduction efforts in planning documents and appropriate budget allocations. Performance measurement does not fully cover specific and sensitive interventions with low achievements. Performance reporting has not been carried out periodically and on time, and performance data has also not been fully used for planning and budgeting for the next period.